Analysis of the Carbon Footprint of Academic Gowns: A Case Study of Thai University - Petchchedchoo, Pattanant; Petcharaks, Nit; Piratrakul, Prashya; Wongmuek, Kamonsiri (Journal of Current Science and Technology, 2024)
The apparel industry has a significant impact on climate change due to the substantial amount of greenhouse gas (GHG) emissions. Academic gowns commonly used in Thailand may be a significant contributor to high GHG levels due to apparel consumption. The objective of this study was to quantify the carbon footprint (CF) of an academic gown for bachelor degree students worn during the commencement ceremony at a private Thai university. The evaluation complies with the national guidelines on Carbon Footprint of Product (CFP) established by the Thailand Greenhouse Gas Management Organization (TGO) in line with ISO 14067:2018 Greenhouse gases - Carbon footprint of products - Requirements and guidelines for quantification. Considering only a single impact category: climate change, GHG emissions were calculated for the entire product life cycle, including raw material acquisition, production process, distribution, use, and the end-of-life (EoL) treatment, and relevant transportation/delivery. Data in this study were collected from the entrepreneur producing academic gowns for rental purposes. The numerical results revealed that CFP of an academic gown with a length of 40 inches, weighing 1,284.30 g, is 42.7 kgCO2-eq over its entire life cycle with 39.71% contributing from use phase and EoL treatment. The stages of raw material acquisition, use phase and production process caused most of the emissions at 41.08%, 33.69% and 18.49%, respectively. The carbon footprint of this gown serves as an important baseline data to enhance design development and the production process for emission reductions.